UPAYA MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS XI IPA 1 SMAN 1 WARINGINKURUNG PADA MATERI KESETIMBANGAN BENDA TEGAR DALAM PEMBELAJARAN DARING MELALUI METODE FLIPPED CLASSROOM - Komarudin, Komarudin (Jurnal Analisis Pendidikan Sosial, 2024)
This research was conducted at SMAN 1 Waringinkurung with the aim of describing the application of the flipped classroom learning method to online learning during the Covid-19 pandemic to increase the learning activities of class XI IPA 1 students on rigid body equilibrium material. The problem that became the background of this research was that the online learning method used during the Covid-19 pandemic was still teacher-centered. The activeness of students in the learning process is still not optimal because students are more inclined to listen and take notes, rarely express their opinions. Discussions between groups are also rarely carried out so that interaction and communication between students and with teachers is still not optimal. This type of research is classroom action research with research subjects consisting of 32 students. Collecting research data using observation methods, student questionnaires, quizzes, and documentation. The research implementation by applying the flipped classroom learning method was carried out in two cycles. In the pre-cycle, the score of student learning activities was 41.25%, cycle 1 was 53.74% and cycle 2 was 83.25%. The results of this study indicate that the use of the flipped classroom learning method in online learning during the Covid-19 pandemic can increase the learning activities of class XI IPA 1 students at SMAN 1 Waringinkurung for the 2021/2022 academic year.